Bullying as a social phenomenon in the modern world - E. A. Danilova; E. V. Shchanina (Вестник университета)
Тhe article discusses approaches to the interpretation and the content of bullying, defines its types and distinguishes the forms of direct and indirect bullying. A comparative analysis of the results of domestic and foreign studies has revealed the spread scale of the bullying phenomenon in modern society, which causes the development of destructive socialization processes. It is emphasized that regular aggressive behavior towards one or a group of persons is a global problem, that is common for all countries of the world. The authors focus on the phenomenon of bullying in the socio-demographic groups of children and youth, which are among the most vulnerable in terms of socialization processes. At the same time, the consequences of bullying for its participants may be not only the deterioration of the physical and mental health of the younger generation, but also a lower socio-economic status in the stratification structure of society. In conclusion, the article concludes that in modern conditions it is necessary to actively develop and implement relevant initiatives of social institutions, which can serve as the basis for the formation of a legislative framework and state programs for the prevention and counteraction of bullying. Consequently, such initiatives will contribute to the formation of a healthy generation.